Respuesta :

frika

Answer:

[tex](x-1)^2+(y-1)^2=37.[/tex]

Step-by-step explanation:

If the center of the circle is (1,1) and the circle passes through the point (2,-5), then the radius of the circle is

[tex]r=\sqrt{(1-2)^2+(1-(-5))^2}=\sqrt{1+36}=\sqrt{37}.[/tex]

The equation of the circle with center [tex](x_0,y_0)[/tex] and radius r is

[tex](x-x_0)^2+(y-y_0)^2=r^2.[/tex]

In your case, the equation is

[tex](x-1)^2+(y-1)^2=37.[/tex]

Answer:

(x-1)²+(y-1)² = 37 is the equation of circle.

Step-by-step explanation:

 We have given the center (1,1) and a point P (2,-5) from which the circle is passes.

So, the radius of the circle is :

r=[tex]\sqrt{(2-1)^{2}+(1-(-5))^{2}}[/tex]

r = [tex]\sqrt{37}[/tex]

The equation of circle is :

(x - x₁)² +(y - y₁)² = r²     where (x₁,y₁) is the center of circle.

Putting the value in above equation we get,

(x-1)²+(y-1)² = (√37)²

(x-1)²+(y-1)² = 37 is the equation of circle.